0.13-0.01(x+1)=0.03(4-x)

Simple and best practice solution for 0.13-0.01(x+1)=0.03(4-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.13-0.01(x+1)=0.03(4-x) equation:


Simplifying
0.13 + -0.01(x + 1) = 0.03(4 + -1x)

Reorder the terms:
0.13 + -0.01(1 + x) = 0.03(4 + -1x)
0.13 + (1 * -0.01 + x * -0.01) = 0.03(4 + -1x)
0.13 + (-0.01 + -0.01x) = 0.03(4 + -1x)

Combine like terms: 0.13 + -0.01 = 0.12
0.12 + -0.01x = 0.03(4 + -1x)
0.12 + -0.01x = (4 * 0.03 + -1x * 0.03)
0.12 + -0.01x = (0.12 + -0.03x)

Add '-0.12' to each side of the equation.
0.12 + -0.12 + -0.01x = 0.12 + -0.12 + -0.03x

Combine like terms: 0.12 + -0.12 = 0.00
0.00 + -0.01x = 0.12 + -0.12 + -0.03x
-0.01x = 0.12 + -0.12 + -0.03x

Combine like terms: 0.12 + -0.12 = 0.00
-0.01x = 0.00 + -0.03x
-0.01x = -0.03x

Solving
-0.01x = -0.03x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.03x' to each side of the equation.
-0.01x + 0.03x = -0.03x + 0.03x

Combine like terms: -0.01x + 0.03x = 0.02x
0.02x = -0.03x + 0.03x

Combine like terms: -0.03x + 0.03x = 0.00
0.02x = 0.00

Divide each side by '0.02'.
x = 0

Simplifying
x = 0

See similar equations:

| (4n-3h)/13=C | | 3(x+3)/4=2x-3 | | 6y^2-6y-12=0 | | -35+7x=-7x-5(1x+7) | | (5/2*1/3+4/5*3/2)*15/2 | | 3(x-2)-10= | | 0.95x+0.05(10-x)=0.10(-139) | | 13+5r=4(1r+5) | | 3v+5/6=4v-6/3+2 | | t=((1-3)d)(60-t) | | (x+3)+9= | | 9+8n=7+2(6+3n) | | 11x+17=2x+287 | | 4w^2+2=-9w | | 1+-2gk=h | | 12x+26=6x+206 | | 38-4x-3.147x=0 | | 18-7x=94 | | 25x^2+9=20 | | 72x-9/2x^2=0 | | 5(3y+4)=14y | | 100x^2+120x+36=0 | | 5(3y-4)=14y | | 7-(x/8)=(x/6) | | 4u^2-11u+6= | | (3c-4)= | | 3x+7=-32 | | 3x^2-2x-21= | | (7y-2)/3=-4/(y-3) | | 10/2p-6/20=15/20p+9/20 | | Ax-1=bx | | 18-4200/x^2 |

Equations solver categories